Gender differences in the impact of leader-member exchange quality on job embeddedness and turnover intention - Wahyudi, Triyono Arief; Hendryadi, Hendryadi; Iskandar, Donant Alananto; Suryani, Suryani; Gustiawan, Deni (Business: Theory and Practice, 2022)
This study aims to explore the gender differences in the relationships between leader-member exchange (LMX), job embeddedness, and turnover intention. Hypotheses formulation was conducted by integrating conservation of resources (COR) theory and social role theory, and data were collected from 462 respondents who were employed in various sectors in Indonesia. Data analyses included confirmatory factor analysis to evaluate the measurement model, followed by mediation-moderation analysis by using the PROCESS macro. As hypothesized, LMX showed a positive impact on job embeddedness and a negative impact on turnover intention. Job embeddedness was negatively associated with turnover intention, partially mediating the relationship between LMX quality and turnover intention. This study showed that gender moderated the relationships between LMX, job embeddedness, and turnover intention; this was particularly evident in the female participants. This study contributes to the literature on the significance of LMX quality and job embeddedness by exploring gender-specific roles, thus strengthening the existing knowledge base.